LYMPHOMATOSIS CEREBRI: A TREATABLE CAUSE OF RAPIDLY PROGRESSIVE DEMENTIA. Issue 11 (14th October 2015) - Samani, Amit; Davagnanam, Indran; Cockerell, Oliver Charles; Ramsay, Alan; Patani, Rickie; Chataway, Jeremy
Abstract : We describe a case of lymphomatosis cerebri (LC), an extremely rare variant of Primary Central Nervous System Lymphoma (PCNSL) characterised by diffuse infiltration of brain parenchyma by a non-cohesive mass of malignant lymphocytes. A 50 year-old lady presented with rapidly progressive cognitive decline. Neuropsychometric testing showed global cognitive deficits with magnetic resonance imaging of the brain showing diffuse T2-weighted white matter hyperintensity. Initial impression included metachromatic leukodystrophy however after a series of normal investigations, and clinicoradiological deterioration, a decision was made to proceed to brain biopsy which showed LC. Following chemoradiotherapy she regained the ability to ambulate independently and her cognitive state improved. PCNSL typically presents as discrete gadolinium-enhancing T2 hyperintense lesions. Very rarely it presents as LC, usually manifest as rapidly progressive cognitive decline and leukoencepahlopathy. Complete remission of LC has been achieved with steroid use followed by radiotherapy, cisplatin or methotrexate. Although there are many causes of rapidly progressive leukoencephalopathy, rapid progression of structural change, perhaps combined with new foci of enhancement, should prompt thoughts of an underlying neoplastic process and the need for biopsy. This case highlights the diagnostic (and potential therapeutic) importance of early consideration of brain biopsy in patients with rapidly progressive atypical neurological syndromes